From Positive Neutrality to Silk Road Activism? The Continuities and Changes in Turkmenistan's Foreign Policy*. Issue 3 (4th May 2018) - Yapıcı, Utku
Abstract: Turkmenistan's foreign policy has been the subject of considerable scholarly debate since the Turkmenistan administration's attempt to acquire a neutral status and the United Nations General Assembly's recognition of this status by a declaration in 1995. This article firstly demonstrates the primary manifestations of Turkmenistan's neutralism and analyses the roots of this foreign policy approach. In this context, the links of the continuities and changes in Turkmenistan's foreign policy to Turkmenistan's domestic politics are addressed. The article also tries to answer the question of whether the current activism in Turkmenistan's foreign policy connotes a rupture from neutrality or not.